HIGH SCHOOL STUDENTS’ ONTOGENIC OBSTACLES IN SOLVING SOLID GEOMETRY PROBLEMS VIEWED FROM SPATIAL ABILITY (Proceedings of the International Conference on Future of Education, 2024)
Many students have difficulties understanding the topic of solid geometry due to their limited knowledge, commonly called ontogenic obstacles. This study aims to investigate what ontogenic obstacles arise when students solve solid geometry problems based on spatial ability indicators. A qualitative with case study approach was applied in this study. Participants of this study were 44 twelve graders in one of the public high schools in Serang, Indonesia. Data collection was carried out through a test consisting of 3 questions related to prerequisite material and 3 questions on solid geometry problems based on spatial ability indicators, observations and interviews with students. The results show that ontogenic obstacles found in this study include psychological, instrumental, and conceptual ontogenic obstacles. First is psychological ontogenic obstacles that occur when students do not like mathematics, so they easily forget the material they have learned. Second is instrumental ontogenic obstacles that occur when students are less prepared in understanding the distance concepts of solid geometry such as distance between point-to-point, point-to-line, and point-to-plane so students are mistaken in solving solid geometry problems based on spatial ability indicators. Third is conceptual ontogenic obstacles that occur when some students do not understand arithmetic operations, so they are confused in solving arithmetic operations related to the problem. Then overall, the ontogenic obstacles that are most often experienced by students include constructing solid figures into the appropriate plane figures, constructing plane figures that are as expected, and completing arithmetic operations.
Keywords: Ontogenic obstacles; Solid geometry; Spatial ability